Water Formation for the Metalation of Porphyrin Molecules on Oxidized Cu(111). Issue 41 (24th August 2016) - Verdini, Alberto; Shinde, Prashant; Montanari, Gian Luca; Suran‐Brunelli, Simone Tommaso; Caputo, Marco; Di Santo, Giovanni; Pignedoli, Carlo A.; Floreano, Luca; Passerone, Daniele; Goldoni, Andrea
Abstract: Herein the formation of water molecules in the intermediate step of the redox reaction of porphyrins self‐metalation on O/Cu(111) is demonstrated. Photoemission measurements show that the temperature on which porphyrins pick‐up a substrate metal atom on O/Cu(111) is reduced by about 185±15 K with respect to the pure Cu(111). DFT calculations clearly indicate that the formation of a water molecule is less expensive than the formation of H2 on the O/Cu(111) substrate and, in some cases, it can be also exothermic. Abstract : In the intermediate step of the redox reaction of porphyrins on O/Cu(111) we demonstrate the formation of water molecules. The metalation of porphyrins with Cu occurs at about 185±15 K with respect to the pure Cu(111). DFT calculations clearly indicate that the formation of a water molecule is less expensive than the formation of H2 on the O/Cu(111) substrate (see figure).